PKM SOSIALISASI PERILAKU HIDUP SEHAT DI MASA PANDEMI COVID-19 PADA PESERTA DIDIK - Wulandari Wulandari (Pusat Riset dan Inovasi Nasional, 2021)
Corona virus is not an epidemic that can be ignored. When viewed from the symptoms, ordinary people will think it's just an ordinary influenza, but for medical analysis this virus is quite dangerous and deadly. Currently, the number of deaths continues to increase. The best preventive effort is to avoid exposure to viruses based on PHBS (Clean and Healthy Living Behavior). Forms of clean and healthy living behavior during this covid pandemic include the use of masks; cover mouth and nose when sneezing or coughing; washing hands regularly with soap or disinfecting them with a hand sanitizer containing at least 60% alcohol; avoiding contact with infected people; keep your distance from people; and refrain from touching the eyes, nose, and mouth with unwashed hands. The role of parental knowledge will affect the formation of health behavior in children, especially in the application of PHBS.